A selective phelix-variant for the real-time encryption of LWC video streams - Butalid, Rachelle (2007)
Improvements in technology and wide access to high-speed Internet have led to greater consumption of streaming multimedia. The recent years have seen a hike in the amount of high-value video data being streamed across the Internet. Many of these services require security from theft and guarantees of confidentiality. [1] describes the Light-Weight Codec (LWC), a codec that may be applied is such services. However, LWC lacks a mechanism to protect itself from security threats. One method of providing security to LWC is to encrypt the stream, making the data worthless for those who access it illegitimately. Unfortunately, encryption can be computationally expensive, and can lead to delayed frames when used on live streams. For real-time video services, this delay is unacceptable and must be minimized. The study remedies this problem by turning to the stream cipher Phelix. Delay is reduced in LWC by implementing an encryption module using a reduced-round variant of Phelix in conjuction with selective encryption techniques. The encryption module was tested in terms of speed and image degradation. Overhead was measured by computing for the average frame-rates of an encrypted stream and an unencrypted stream, using clock cycle costs. A minimum loss of 0.27072 frames per second was recorded. When bench-marked against the AES in counter mode, a maximum gain of 4.83195 frames per second was measured. Screen shots of encrypted videos showed that the images were distorted and visually incoherent.